The difference of students’ learning outcomes with project based learning using handout and sway Microsoft 365 - Nelius Harefa; Novia Fransisca Dewi Silalahi; Elferida Sormin; Leony Sanga Lamsari Purba; Sumiyati Sumiyati (Pascasarjana Universitas Negeri Medan, 2019)
This study aimed to determine the difference of students’ learning outcomes with project based learning using handout and sway Microsoft 365. The sample was selected using purposive sampling into experimental group I and experimental group II with 64 students. The experimental group I used the project based learning using sway Microsoft 365, while the experimental group II used the project based learning using handout. The difference test between experimental group I and experimental group II student tcount (5.411) > ttable (2.425) at significance α = 0.05, it concluded that there was the difference of students’ learning outcomes used project based learning using handout and sway Microsoft 365.Keywords:Handout; learning outcomes; project based learning; sway Microsoft 365